Visions d'Orient : des cites mesopotamiennes a la Jerusalem des croises : la donation Camille Aboussouan - Lintz, Yannick.; Niviere, Marie-Dominique.; Amandry, Michel.; Aboussouan, Camille. (Reunion des musees nationaux ; Musee des beaux-arts d'Agen, 2002)
Accompanying CD-ROM contains indexed color reproductions and descriptive text for over 1600 objects in the Aboussouan collection.